2021
DOI: 10.1101/2021.12.03.471057
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unconventional secretion of unglycosylated ORF8 is critical for the cytokine storm during SARS-CoV-2 infection

Abstract: Coronavirus disease 2019 is a respiratory infectious disease caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Evidence on the pathogenesis of SARS-CoV-2 is accumulating rapidly. In addition to structural proteins such as Spike and Envelope, the functional roles of non-structural and accessory proteins in regulating viral life cycle and host immune responses remain to be understood. Here, we show that open reading frame 8 (ORF8) acts as messenger for inter-cellular communication betwe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…These clinical evidence indicates that the orf8 gene in SARS-CoV-2 does not fully correlate with viral pathogenicity and disease severity. Interestingly, Lin et al have reported that the unglycosylated ORF8 secreted via an unconventional pathway is responsible for the COVID-19 cytokine storm through IL-17 receptor-based signaling ( 31 , 56 ). However, their proposed mechanism seems contradictory to the recent clinical evidence.…”
Section: Discussionmentioning
confidence: 99%
“…These clinical evidence indicates that the orf8 gene in SARS-CoV-2 does not fully correlate with viral pathogenicity and disease severity. Interestingly, Lin et al have reported that the unglycosylated ORF8 secreted via an unconventional pathway is responsible for the COVID-19 cytokine storm through IL-17 receptor-based signaling ( 31 , 56 ). However, their proposed mechanism seems contradictory to the recent clinical evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Our work confirms findings from previous studies, including our own, that described an interaction between Spike and ORF8, a reduction in Spike pseudovirus particle productions, but also, importantly, extends our knowledge by showing ORF8 targeting viral particle productions and causing Golgi fragmentations using live virus, replicon, and VLP. While we contribute significant knowledge in VLP, replicon and virus-infected cells, our study also opens several new areas of study.. Our model is that in SARS-CoV-2, which has intact ORF8 or produces signal peptides of ORF8, viral particle production is dampened, possibly as a way to reduce immunosurveillance of infected cells (14,16,30) or or as an unwanted effect of ORF8's other functions benefitting viral replication (8,9,18) (Fig 5E). In ORF8-deficient SARS-CoV-2, viral particle production is not disrupted, leading to increased viral particle formation (Fig 5E).…”
Section: Discussionmentioning
confidence: 98%
“…ORF8 signal peptide may be behaving in a similar way as NS1. Like NS1, ORF8 can be secreted by conventional and unconventional secretory pathways (14,33).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations